Simulating compliance behaviour for effective inspection strategies using agent based modelling. Issue 4 (4th April 2016) - van Asselt, Esther; Osinga, Sjoukje; Bremmers, Harry
Abstract : Purpose: – The purpose of this paper is to simulate compliance behaviour of entrepreneurs in the Netherlands based on the Table of Eleven: 11 factors determining compliance (based on economic, cognitive, social and institutional factors). Design/methodology/approach: – An Agent-Based Model (ABM) was developed that could incorporate both individual and group behaviour and allowed to evaluate the effect of various intervention strategies. For this purpose, a case study on the compliance of pig farmers with antibiotics legislation in the Netherlands was used. Findings: – The effect of social factors (acceptance of legislation and social influence) on compliance levels was tested as well as the number of inspectors. This showed that the model can help to choose the most optimal intervention strategy depending on the input parameters. Research limitations/implications: – Further expansion of the model may be necessary, e.g. including economic factors, in order to reflect real-life situations more closely. Practical implications: – The model can be used by inspection services to effectively implement their control programme. Originality/value: – The developed ABM is a first attempt to simulate compliance behaviour and as such contributes to the current limited knowledge on effective intervention strategies.